The Roles of Performing Arts in Depression Care at KATH: Towards a Culturally Sensitive Model - Gloria Esi Kportufe; Dickson Adom; Ruth Owusu-Antwi; Steve Kquofi (Yayasan Keluarga Guru Mandiri, 2025)
In most developing countries like Ghana, very little attention is paid to depression due to the lack of mental health education, which has resulted in the high levels of stigmatization faced by persons living with cognitive conditions. Coupled with the negative perceptions about the condition, the few mental health facilities in the country are under-resourced. This study aimed to identify the existing depression treatment models at Komfo Anokye Teaching Hospital (KATH) and examine the roles of selected performing arts in depression care to guide the creation of a culturally sensitive depression treatment model. Primary data for this qualitative phenomenological study were gathered from five persons with depression, five mental healthcare professionals of the KATH Psychiatry Unit, and two cultural experts from the Centre for National Culture, Kumasi. Findings in this research indicated that a culturally sensitive model at KATH, employing performing arts, could enhance the moods of persons with depression, improve their outcomes, and reduce their hospital stay, boost their self-esteem and social interaction. Incorporating a culturally sensitive model into depression care at KATH to augment the existing treatment models has been established to be a revolutionary development in mental healthcare delivery at KATH.